Bending performance of dapped-end beams having web opening: Experimental and numerical investigation. (February 2023) - Aksoylu, Ceyhun; Özkılıç, Yasin Onuralp; Çeledir, Emrullah; Arslan, Musa Hakan
Abstract: Reinforced concrete dapped-end (purlin) beams are frequently used in prefabricated industrial structures. The main task of these beams is to safely carry the loads on the roof. Considering the number of these purlin beams in industrial buildings, it is extremely important for manufacturers to product these beams with less concrete without reducing the load carrying capacity. Since these purlin beams are under the effect of bending and shear forces, controlled creating openings in beam span can have significant economic benefits for the manufacturer. Therefore especially economic design perspective, it is so crucial to determine the amount of openings that will not cause a significant change in the bending behavior. In this study, the behavior of dapped-end purlins with openings was experimentally and numerically investigated. In the experimental step, seven purlin beams having different opening configurations were tested under four-point loading to investigate the openings effects on beam structural behavior. In this step opening length to total length varying between 0.075 and 0.325 was selected as a main parameter. After test, the numerical models were created and verified using experimental findings. After this step, in the parametric study part of the paper, the effects of shear span, depth of the opening and length of opening and different opening configurations (such as segmentation) which were not tested in experiments, were examined. The experimental outcomes revealed that increases in the opening did not provide a significant effect on the load capacity. This can be explained by the fact that the openings are in the bending region. The numerical findings showed that increasing shear span to depth ratio (av /d) ratio did not change rigidity but decreased the load capacity. However, no effect was observed on the opening height provided that it is at least as far away from the upper and lower longitudinal reinforcements bars as the concrete-cover margin. On the other hand, increasing opening/purlin length (especially higher than 0.375) reduces the capacity. However, segmented openings (multiple openings instead of single whole openings) did not reduce capacity even if total opening/purlin length was 0.525.